Recognition of the structural distortions at the junctions between B and Z segments in negatively supercoiled DNA by osmium tetroxide - Nejedlý, K; Kwinkowski, M; Gałazka, G; Kłysik, J; Palecek, E (Journal of biomolecular structure & dynamics, 1985)
It has been shown for the first time that conformational junction between contiguous right-handed B and left-handed Z segments can be recognized by a chemical probe. Plasmid pRW751 containing (dC-dG)13 and (dC-dG)16 blocks was treated with osmium tetroxide, pyridine (a reagent known to be single-strand selective) at physiological ionic conditions (0.1 and 0.2 M NaCl) and neutral pH. Mapping of the osmium binding sites by restriction enzyme digestion followed by nuclease S1 cleavage has revealed selective binding of osmium at, or near to, the end of the (dC-dG)n segments proximal to the 95 bp lac sequence. The junction of the shorter (dC-dG)13 segment was modified to a substantially greater extent than that of the longer segment. Partial inhibition of DNA cleavage by BamHI was observed at the restriction sites neighbouring to the both (dC-dG)n segments as a result of DNA modification by osmium tetroxide. The site-selective modification occurred only in supercoiled and not in relaxed molecules. Differences in the sensitivity of the B/Z junctions in pRW751 to the osmium tetroxide were explained by different structural features of these junctions.
Keywords: molekulární struktura; Restriction Mapping; restrikční mapování; konformace nukleové kyseliny; plazmidy; Nucleic Acid Conformation; Osmium Tetroxide; DNA, Superhelical; superhelikální DNA; Binding Sites; oxid osmičelý; Plasmids; DNA; vazebná místa; Molecular Structure